Role of Women in Provincial Assembly of Punjab (2008-2018) - Munawar, Aqsa; Hanif, Kalsoom; Aziz, Sumaila (Annals of Human and Social Sciences, 2024)
Despite making up half of the world’s population, women are rarely depicted in proportion to their numbers. This underrepresentation is pervasive in all socioeconomic domains as well as in all cultures. Women still face discrimination, particularly in the political sphere, regardless of geography. It aims to assess the extent of genuine female political participation Pakistan has experienced since becoming independent. In this research woman participation in one of the important institutions of Pakistan is analyzed. Women role in Punjab legislative Assembly from 2008-2018 will be focused. Women side by side with the male counterpart took part in every field where legislation was needed like education and health sectors. The article examines the proportion of women appointed to positions of authority and evaluates their contributions to the legislative process with a focus on the introduction of bills and resolutions concerning women’s rights in order to complete the aforementioned goal. This article is qualitative research. Primary and secondary data will be used. Data gathered from Punjab Assmbly. The results show that women are not fairly represented in decision-making roles within the Punjab Assembly. With a few exceptions, the majority of female parliamentarians remained idle and inoperative for their entire term. They couldn’t actively participate in the legislative process as a group. They continued to do a poor job of advocating for the rights of their own gender community.